Ecological applications : - Townsend, Colin R. (Blackwell, 2008)
“I think this text will be extremely useful and popular with the students …The overall tone of the book is lively, warmly humorous, engaging, and clear.” Dr Anita Diaz, Bournemouth University“<!--end-->